Perancangan Blog Guru untuk Penyediaan Bahan Ajar di Era Pembelajaran Abad 21 - Nurmida Catherine Sitompul; Rufi’i; Ibut Priono Leksono; Heri Wahyu Rejeki (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2021)
Now a day world is changing complexity and unpredicted which as characteristic in 21st century. These conditions asked severals solutions which more complex according to context. The purpose of education reformulated its goal that to prepare students to be a problem solver. Teaching with problem base learning needs many kinds of learning resources. All these kinds of information will be used of the students to analyses the problems from many points of views. Blog is one of application can be provided informations/datas. Fortunately, almost all schools ini city have already have computers and internets facilitation, but still do not use yet for learning. The purpose of this activity is to train teachers to desing and create their own Blog to facilitate student’s learning. The result showed that all teachers can create a Blog for their Subject. For the future Teacher BLOG should be develop regulary